Effects Of Induction Heating On Thixoformed MWCNT-Al Alloy Composite - Salleh, Mohd Shukor; Mohammad Ali, Nur Fatihatur Rawdhah; Yahaya, Saifudin Hafiz; Al-Zubaidi, S.S. (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
The aim of this paper is to investigate the effect of vertical induction heating on MWCNT-Al alloy composite during thixoforming. Several feedstocks of MWCNT-A356 alloy composite with a non-dendritic microstructure were prepared using a mechanical stirring of liquid casting. During thixoforming, the feedstocks were reheated up to the 50 % liquid fraction in the semi-solid state at 580 °C and compress into an upper mold. The heat distribution is determined by analyzing the microstructures and densities throughout the cross-sectional of the feedstock. After that, real time temperature monitoring is carried out using the EPAD-Base2 data acquisition systems, optical microscopic observations and electronic densimeter measurements were used, respectively at its surface, top, center, and bottom locations. The results show that the temperatures distribution is consistent with only ± 10 °C variation. The homogeneous heat distribution has also been observed by the similar coarsening rates of α-Al grain after thixoforming with the average grain diameter of 37.9 ± 22.8 µm and spherical factor (SF) of 0.564 ± 0.127, and the densities are almost identical of 2.675 ± 0.009 g/cm3, 2.676 ± 0.011 g/cm3 and 2.676 ± 0.007 g/cm3 at these locations. Therefore, the vertical induction heating in this study is suitable for thixoforming of the composite aluminium alloy.